Gamma radiation for in vitro mutagenesis in banana, cultivar Terra Maranhão - Pestana, Rosa Karla Nogueira; Amorim, Edson Perito; Silva, Sebastião de Oliveira e; Neto, Augusto Tulmann (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the survival of plants and shoots as well as the reduction in the height of banana cultivar Terra Maranhão in gamma rays doses. In vitro plants were irradiated with different gamma rays doses – 0, 20, 30, 40 e 60 kGy – and afterwards their multiplication rate was evaluated. The doses of 20 and 30 kGy were the most indicated for use in the Terra Maranhão cultivar, since these irradiation intensities enabled greater values for the number of buds and survival index.